Effect of reinforcement volume fraction on the mechanical properties of the Al-SiC nanocomposite materials - Iqbal, AKM Asif; Norul Amierah, Nor Zamani (IOP Publishing, 2017)
Particle reinforced metal matrix composites (MMCs) has emerged as one of the potential materials for structural application due to their superior mechanical properties. However, these MMCs have poor damage tolerance due to their low fracture toughness. The volume fraction of reinforcement plays a significant role to improve the overall strength of the MMCs. In this research, Al matrix composites reinforced with three different volume fraction of the SiC nanoparticles were fabricated by a powder metallurgy process and the effects of volume fraction on the mechanical properties of the Al-SiC nanocomposite was investigated. The samples were prepared with 200 kN compaction load and 600°C sintering temperature. Subsequently, their mechanical testing was carried out. The density and hardness of the samples were investigated. Moreover, the microstructure of the nanocomposites was examined by optical microscope. The results showed that the high volume fraction reinforced nanocomposite exhibited better microstructural feature and high hardness as compared to the low volume fraction reinforced nanocomposite. Therefore, the high volume fraction reinforced nanocomposite can be a potential material to use in the brake disc of the automobile.